Patient experience surveys for children's community health services: A scoping review. (March 2022) - Nelson, Helen J; Pienaar, Catherine; Williams, Anne M; Munns, Ailsa; McKenzie, Katie; Mörelius, Evalotte
Patient experience surveys have a user focus and measure the quality of person-centered health care for hospital inpatients and consumers of community health services, providing a governance process to evaluate the quality of care and to action improvement. Experience of care has been described as effective communication, respect and dignity, and emotional support. Measurement criteria for these domains are not standardized, leading to inconsistent reporting of patient experience. The objective of this scoping review was to synthesize evidence for measuring experience of care in children's community health services using the Joanna Briggs Institute framework for scoping review method. Three parent-reported surveys met the inclusion criteria, and 50 survey items were assessed by expert reviewers for fit to domains of healthcare experience. Conceptual domains of parent experience in children's community health services included respect and dignity, effective communication, and emotional support. A gap was identified, in that few items in identified surveys measured emotional support. This contribution will promote consistent reporting of healthcare experience, informing policy and practice for person-centered health care.